King Abdullah, Britain, and the making of Jordan - Wilson, Mary C. (Mary Christina) 1950- (Cambridge Middle East library, 1987)
The first in-depth study of the historical and personal circumstances that made King Abdullah such a controversial figure in modern Middle East history